2013
DOI: 10.1105/tpc.113.114462
|View full text |Cite
|
Sign up to set email alerts
|

The BRASSINOSTEROID INSENSITIVE1–LIKE3 Signalosome Complex Regulates Arabidopsis Root Development    

Abstract: Brassinosteroid (BR) hormones are primarily perceived at the cell surface by the leucine-rich repeat receptor-like kinase BRASSINOSTEROID INSENSITIVE1 (BRI1). In Arabidopsis thaliana, BRI1 has two close homologs, BRI1-LIKE1 (BRL1) and BRL3, respectively, which are expressed in the vascular tissues and regulate shoot vascular development. Here, we identify novel components of the BRL3 receptor complex in planta by immunoprecipitation and mass spectrometry analysis. Whereas BRI1 ASSOCIATED KINASE1 (BAK1) and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 49 publications
3
85
1
Order By: Relevance
“…In contrast to the results with bri1 cnu1 , RLP44 overexpression was able to rescue the phenotype of the bak1-4 mutant (30, 31) (Fig. 3 F and G), possibly reflecting the different levels of genetic redundancy in the BRI1-like and BAK1/SERK gene families (32,33): BAK1/ SERK3 is partially redundant with SERK1 and SERK4, and a bri1 null-like phenotype is only observed in the absence of all three SERKs (33). Thus, RLP44-mediated rescue of bak1-4, but not of bri1 cnu1 might be explained by a possible interaction of RLP44 with the two other redundant SERKs (see below).…”
Section: Loss Of Rlp44 Function Prevents Activation Of Br Signaling Bcontrasting
confidence: 47%
“…In contrast to the results with bri1 cnu1 , RLP44 overexpression was able to rescue the phenotype of the bak1-4 mutant (30, 31) (Fig. 3 F and G), possibly reflecting the different levels of genetic redundancy in the BRI1-like and BAK1/SERK gene families (32,33): BAK1/ SERK3 is partially redundant with SERK1 and SERK4, and a bri1 null-like phenotype is only observed in the absence of all three SERKs (33). Thus, RLP44-mediated rescue of bak1-4, but not of bri1 cnu1 might be explained by a possible interaction of RLP44 with the two other redundant SERKs (see below).…”
Section: Loss Of Rlp44 Function Prevents Activation Of Br Signaling Bcontrasting
confidence: 47%
“…(Scale bar, 50 μM.) three BR receptors (12), revealed unequal redundancy between these receptors. Stele-localized BRI1 had the most significant impact on restraining the extent of stem cell daughter proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, enhanced BR signaling triggered by impaired spatial distribution of BRI1, limits cell elongation and whole root growth (11). BRs are also perceived by BRI1-Like 1 (BRL1) and BRI1-Like 3 (BRL3), two BRI1 homologs that are confined to the stem cell niche and the stele, where they promote QC cell divisions (12)(13)(14). BRI1 acting in the epidermis promotes stem cell daughter divisions, stimulating root meristem size and whole root growth via an unknown signal (9).…”
mentioning
confidence: 99%
“…Accordingly, we found that sd1 had longer roots while GA20-1ox had shorter roots compared with their respective wild types. Considering the unchanged root length in d2, d11, and even brd1, the most severe BR-deficient mutant (Supplemental Table 1) (Mori et al, 2002), rice root systems may have more complex mechanisms than aerial tissues that regulate growth (González-García et al, 2011;Fàbregas et al, 2013).…”
Section: Decreased Sensitivity Of Ga Mutants To Exogenous Br Inhibitimentioning
confidence: 99%